Embracing innovation framework and transformative paradigm: A practical application in the ultralight project - Widiasih, Restuning; Pramukti, Iqbal; Aini, Farah Huwaida Qurrota; Popoola, Tosin (Jurnal Keperawatan Padjadjaran, 2024)
Higher education, as a centre for research and innovation in the era of transformative learning, is encouraged to conduct research and innovation that can lead to innovation and impact in the areas of health, economy, and sustainability. Innovation requires a framework that functions as an essential guide for development. However, limited innovation frameworks can be applied in nursing, including maternity nursing. This study discusses the M-Motion framework as an alternative framework for developing maternity nursing innovation research. M-Motion comprises of three steps of: pre-innovation, innovation, and post-innovation and it is applied to the Ultralight Project. The project aims to improve pregnancy and fetal health by using the DetectMe device to integrate mothers’ self-monitoring data into online health systems so that the condition of pregnant women and their babies is promptly and accurately monitored. The application of the M-Motion framework to the Ultralight Project is a step in the right direction as it helps in illustrating the sequence between research and innovation, especially as it relates to the acceleration of reducing maternal and fetal mortality rates.